COMT Val158Met Polymorphism Is Associated with Verbal Working Memory in Neurofibromatosis Type 1 - Costa, Danielle de Souza; de Paula, Jonas J.; Alvim-Soares, Antonio M.; Pereira, Patrícia A.; Malloy-Diniz, Leandro F.; Rodrigues, Luiz O. C.; Romano-Silva, Marco A.; Miranda, Débora M. de (Frontiers in Human Neuroscience, 2016)
Neurofibromatosis type I (NF1) is a neurogenetic disease marked by multiple cognitive and learning problems. Genetic variants may account for phenotypic variance in NF1. Here, we investigated the association between the COMT Val158Met polymorphism and working memory and arithmetic performance in 50 NF1 individuals. A significant association of the COMT polymorphism was observed only with verbal working memory, as measured by the Digit Span Backward task with an advantageous performance for Met/Met carriers. To study how genetic modifiers influence NF1 cognitive performance might be of importance to decrease the unpredictability of the cognitive profile among NF1 patients.